Apertureless Cantilever‐Free Pen Arrays for Scanning Photochemical Printing. Issue 8 (14th October 2014) - Zhou, Yu; Xie, Zhuang; Brown, Keith A.; Park, Daniel J.; Zhou, Xiaozhu; Chen, Peng‐Cheng; Hirtz, Michael; Lin, Qing‐Yuan; Dravid, Vinayak P.; Schatz, George C.; Zheng, Zijian; Mirkin, Chad A.
<x xml:space="preserve">Abstract</x> A novel, apertureless, cantilever‐free pen array can be used for dual scanning photochemical and molecular printing. Serial writing with light is enabled by combining self‐focusing pyramidal pens with an opaque backing between pens. The elastomeric pens also afford force‐tuned illumination and simultaneous delivery of materials and optical energy. These attributes make the technique a promising candidate for maskless high‐resolution photopatterning and combinatorial chemistry. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>